Prognostic value of receptor status change following neoadjuvant chemotherapy in locally advanced breast cancer. (2015) - Ozmen, Vahit; Atasoy, Ajlan; Bozdogan, Atilla; Dincer, Maktav; Eralp, Yesim; Tuzlali, Sitki
Abstract: Introduction : The effect of neoadjuvant chemotherapy (NAC) on the expression of receptor status in locally advanced breast cancer (LABC) is still under investigation. Aims of this study are to evaluate changes in hormone receptor (HR) and HER-2 status post-NAC and correlation with survival. Materials and methods : LABC patients who received NAC between 2001 and 2008 at Istanbul University were analyzed retrospectively. Patients with pathologic complete response (pCR) were excluded in analysis. Immunohistochemical (IHC) analyses was performed on both initial biopsies and surgical specimens. Results : The median age of 128 patients was 48 years and 55% of them were premenopausal. Most of the patients had invasive ductal (81%) and histologic grade (HG) III (81%) breast cancer. Partial pathologic response (pPR) rate was 86.7%. HR status changed in 36 patients (28%). The rates of ER, PR and HER-2 receptor positivity at diagnosis and after NAC were 44–32.8%, 43–29.7%, and 24–21%, respectively. Negative-to-positive change in HR status was observed in five patients. The 5-year overall survival (OS) was 76% in patients whose HR status converted to negative, compared with 91% in patients who remained HR-positive ( p <0.05). Multivariate Cox regression analysis showed that receptor status change was independently related to disease-free survival (DFS) (Hazard Ratio 6.88; p =0.002), whereas as it did not have any impact on OS ( p =0.148). Conclusion : NAC induced changes in HR and HER-2 expression, predominantly from positive to negative. These changes were associated with shorter DFS. Postoperative re-evaluation of receptor status may have clinical significance.